Analysis of the Relationship between Food Consumption Patterns and Food Security among Maize Farmers in Abeli District - Ericha Masitta Dewi R; Sitti Aida Adha Taridala; Samsul Alam Fyka (International journal of technology and education research, 2025)
This research aims to determine: food consumption patterns and food security of corn farmers in Abeli District, Kendari City. This research was conducted in Abeli District, Kendari City with a total sample of 27 respondents. The data analysis used was descriptive statistical analysis using the Likert scale method, USDA analysis, and Rank-Spearman correlation analysis. The research results show that 1) the majority of respondents consume quite high amounts of food, in the categories 4-6 times a week and 1 time a week. Most respondents felt that the food they consumed was neither too much nor too little, indicating adequacy and good adjustment to the number of portions of food they took. On the other hand, the majority of respondents had access or the habit of consuming various types of food other than corn in their diet, 2) the majority of respondents stated that the food choices available were quite varied (59.25%), and had good access to various types of food in the local market (74.07%). All respondents consumed various types of food other than corn every day. all respondents process their own harvests to make daily food, reflecting strong practices in using local food resources to meet family consumption needs, and 3) there is a moderate positive relationship between the frequency of food consumption and the level of food security of respondents, but the relationship between the amount of food portions and food security is not statistically significant. Meanwhile, there is a significant relationship between the variety of food consumed by respondents and the level of food security. In other words, the higher the level of food variety consumed, the higher the level of food security that can be expected from respondents